Figurative Language on Digital Children’s Literature in Website Poems of Poets.Org with Nature and Environment Theme - Putri, Nurul Aulia; Marlina, Leni (Universitas Negeri Padang, 2023)
Figurative language is defined as a means of expressing something other than the usual language in a way that is both meaningful and deeper. This implies understanding the relationship between meaning and sentence, as well as which sentences contain meaning and which do not. This research provides information about figurative language that are found in Poets.org. This research focused only for hyperbole type because researchers want to see how important hyperbole is in children's poetry. The aim of this research is to find how many poems in Nature and Environment themes in the website Poets.org. Additionally to find how many hyperboles that are found and classify the type of meaning that appeared. The data in this research were taken from the hyperbole sentences on 11 poems in Nature theme and 6 poems in environment theme. This research used the descriptive qualitative research method. To conduct this research, the theory of figurative language from Abram (1999 : 120-311) was used. The result shows that there are 14(56%) line of hyperbole found in Nature theme and 11(44%) line of hyperbole found in Environment theme. After obtaining the results of hyperbole, the researcher also found that there are 4 types of meaning found from each hyperbole line, there are affective meaning with 2 occurrence (8%), conceptual meaning with 16 occurrence (68%), connotation meaning with 5 occurrence (20%), and social meaning with 1 occurence (4%). Hyperbole often found in children's poetry on the poets.org with Nature theme and the conceptual meaning is the most common found. Hyperbole is often found in children's poetry on the poets.org website. This research shows that digital children's literature on poetry has a significant impact in knowing the type of figurative language especially hyperbole and the meaning on the poetry website Poets.org with nature and enviroment theme .